Answer:
f ( - 2 ) = - 12
Step-by-step explanation:
f ( - 2 ) = - 3 ( -2 )^2
then you do the exponent first so
- 3 ( 4 )
now you multpily the - 3 and 4
you get - 12
B)
To go from fig. 1 to fig.2 you would dialate 1:3, or 3 times the size
c)
The opposite would be true since you are going the opposite direction. 3:1, 1/3 of the size
Hope this helps:)
You divide the numerator by the denominator, meaning you divide 32 by 3.
+ <span>The vertex of a parabola is (3,2),
that means the parabola's equation is y=a(x-3)</span>²+2
+ <span>A second point on the parabola is (1,5) and we replace x=1 and y=5. We have:
5</span>=a(1-3)<span>²+2 , so we have 4a=5-2 or a=3/4
So the equation is y=3/4 (x-3)</span>²+2
And by checking we have the point (5;5) is on the parabola
Have fun
Seven hundred and forty one
Hope this helps!